Southern Water, Southern Power : How the Politics of Cheap Energy and Water Scarcity Shaped a Region - Manganiello, Christopher J., 1973- (Book collections on Project MUSE., 2015)
Why has the American South become embroiled in intrastate wars over water? Why did unpredictable flooding come to characterize southern waterways, and how did the region become derailed by drought and regional squabbling? To answer these questions, Christopher J. Manganiello moves beyond the well-known accounts of flooding in the Mississippi Valley and irrigation in the West to reveal the contested history of southern water.